2018
DOI: 10.1021/acs.macromol.8b01635
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Membrane Permeability by Increasing the Polymer Crystallinity: The Unique Case of Polythiophenes

Abstract: It is generally accepted in membrane technology that crystalline zones in polymeric membranes do not contribute to transport of liquids nor gases. In current study, poly(3alkylthiophene)s (P3ATs), i.e. homopolymers and random copolymers, were synthesized to study the influence of the supramolecular organization on membrane gas separations. The monomers were polymerized via KCTCP and GPC analysis shows that the polymers have a narrow dispersity. DSC analysis of the polymers reveals that the homopolymers, in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In reality, membranes will have some amount of disorder that may smear out some effects; however, we do not observe less complex behavior in a more disordered array of dense attractive sites [43]. A recent paper, however, demonstrated that the permeability of a polymer membrane increased by orders of magnitude when the polymer crystallizes and is more ordered [50]. The amount of order therefore may be in principle an important tuning parameter.…”
mentioning
confidence: 77%
“…In reality, membranes will have some amount of disorder that may smear out some effects; however, we do not observe less complex behavior in a more disordered array of dense attractive sites [43]. A recent paper, however, demonstrated that the permeability of a polymer membrane increased by orders of magnitude when the polymer crystallizes and is more ordered [50]. The amount of order therefore may be in principle an important tuning parameter.…”
mentioning
confidence: 77%
“…It is generally accepted that the permeability of polymer membranes decreases with an increase in the degree of crystallinity of polymers, as the crystalline zones in polymeric membranes do not contribute to the transport of gas molecules [82]. However, there are few exceptions where the trend is the opposite [83][84][85].…”
Section: Physico-chemical Property Evaluationmentioning
confidence: 99%
“…In addition, crystalline NCPs do not have high gas solubilities and diffusivities. 8 Recently, some amorphous liquid and glassy coordination polymers (CPs), which can be used for hybridization of materials, have been synthesized by using thermal and nonthermal methods. 9 Some glassy CPs can be obtained by employing a melt-quenched method, which is effective in preparing composites composed of inner crystalline PCPs and outer glassy CPs, which do not contain grain boundaries that cause pinholes and have good adhesiveness between each component.…”
Section: Introductionmentioning
confidence: 99%
“…For example, crystalline NCPs are not suitable for use as gas separation media because of difficulties with creating defect-free single crystals of these materials around PCPs and coating by many crystallites results in the formation of pinholes. In addition, crystalline NCPs do not have high gas solubilities and diffusivities …”
Section: Introductionmentioning
confidence: 99%